Strategi Komunikasi Pemasaran Global Dove Melalui Campaign For Real Beauty Dalam Membangun Consumer Engagement Dan Brand Equity - Siti Khodijah Nurfizri; Hansen Mayhell; Dewi Anggrayni (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2026)
Abstract This study aims to analyze Dove's global marketing communication strategy through the Campaign for Real Beauty and examine its role in building consumer engagement and brand equity. The research employs a Literature Review method by reviewing various relevant journal articles, academic books, and scientific publications on global marketing communication, Integrated Marketing Communication (IMC), consumer engagement, and brand equity. The results of the study indicate that the success of the Campaign for Real Beauty is supported by the implementation of a global marketing communication strategy that integrates various communication channels through an IMC approach. Dove consistently maintains its core message of authentic, inclusive, and diverse beauty across various countries, while simultaneously adapting to local cultural contexts. This strategy has successfully built consumer engagement across cognitive, emotional, and behavioral dimensions through messages that resonate with the issues of self-acceptance and women's diversity. Furthermore, this campaign contributes to strengthening brand equity by increasing brand awareness, shaping a positive brand image, reinforcing brand loyalty, and creating strong brand resonance. The research findings also show that social value-based campaigns (purpose-driven marketing) have the capability to build long-term relationships between brands and consumers, although challenges such as consumer skepticism and category inertia remain factors that need to be considered. This study contributes to the development of global marketing communication studies and provides practical implications for companies in designing effective communication strategies in the international market. Keywords: Komunikasi Pemasaran Global; Integrated Marketing Communication (IMC); Campaign for Real Beauty; Brand Equity Dove; Purpose-Driven Marketing